On Leibniz algebras, whose subideals are ideals - Kurdachenko, L.A.; Subbotin, I.Ya.; Yashchuk, V.S. (Доповіді НАН України, 2017)
We obtain a description of solvable Leibniz algebras, whose subideals are ideals. A description of certain types of Leibniz T-algebras is also obtained. In particular, it is established that the structure of Leibniz T-algebras essentially depends on the structure of its nil-radical.